READING LITERACY AND METACOGNITIVE STRATEGY FOR PREDICTING ACADEMIC ACHIEVEMENT - Siti Mahmudatul Banat; Adi Cilik Pierewan (LITERA, 2019)
The importance of  reading literacy is shown in the results of achievement among international countries. Reading literacy has not become a culture for most students. Some students have not used reading strategies to improve their understanding. This will affect the academic achievement. This expost facto research design aims to examine: (1) wether reading literacy can predict academic achievement in knowledge and skill, (2) wether metacognitive strategy can predict academic achievement in knowledge and skill, and (3) wether reading literacy and metacognitive strategy together can predict academic achievement on knowledge and skill.  The population is 543 students of three pilot senior high schools of Curriculum 2013 in Kulon Progo. The sample is 359 students established using the Table of Isaac and Michael. The instrument used is a questionnaire. The result is as follows. (1) Reading literacy can predict academic achievement in knowledge, but it cannot predict academic achievement in skill. (2) Metacognitive strategy can predict academic achievement in knowledge and skill. (3) Reading literacy and metacognitive strategy simultaneously can predict academic achievement on knowledge and skill. Therefore literacy habituation and the use of metacognitive strategies are strongly recommended to improve academic achievement of knowledge and skills.